CHALLENGE AND OPPORTUNITY OF MARKETING MODEL ANALYSIS BASED ON BIG DATA ERA - 丽, 盛 (Chinese Language and Culture Journal, 2017)
With the rapid development of Internet technology in China, the era of big data has arrived. The era of big data has changed the people's consumption concept, and brought new opportunities and challenges to the development of enterprises. Therefore, under the background of big data era, how to explore a more efficient marketing model has become an important topic for enterprises to develop themselves. In this paper, through the analysis of the concept and characteristics of the era of big data, clear the important significance of the era of big data marketing mode, analyzes the era of big data in the background of the current marketing mode, and the challenges and opportunities in the era of big data on marketing mode have been analyzed, in order to explore the future of enterprise marketing model innovation.